2018
DOI: 10.1016/j.joca.2018.02.351
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNA 144 in osteoarthritis

Abstract: versus OOA; SNORD74 and SNORD77. The latter was accompanied by an increase in GAS5 expression in OA. P53 signalling has been implicated in cartilage ageing and OA. The expression of SNHG1, which along with its intronic snoRNAs have previously been identified as being repressed by p53 activation was reduced in ageing and increased in OA in parallel with one of its intronic snoRNAs SNORD26. HAGR identified eight agerelated host genes, including RLP13A, RPS12 in Y versus ON contrast. Six host genes were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…In the present study, IL-1β induction was used to establish the OA chondrocyte model, and qRT-PCR results showed that LINC01534 was also highly expressed in the OA chondrocyte model. Studies have found that lncRNA can be used as a ceRNA to bind miRNA, thereby inhibiting the function of miRNA and affecting the pathogenesis of OA (25). MiR-140-5p is not only abnormally expressed in various tumor tissues, but also involved in the pathogenesis of rheumatoid arthritis and knee osteoarthritis (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, IL-1β induction was used to establish the OA chondrocyte model, and qRT-PCR results showed that LINC01534 was also highly expressed in the OA chondrocyte model. Studies have found that lncRNA can be used as a ceRNA to bind miRNA, thereby inhibiting the function of miRNA and affecting the pathogenesis of OA (25). MiR-140-5p is not only abnormally expressed in various tumor tissues, but also involved in the pathogenesis of rheumatoid arthritis and knee osteoarthritis (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that lncRNA can be used as a ceRNA to bind miRNA, thereby inhibiting the function of miRNA and affecting the pathogenesis of OA. 25 MiR-140-5p is not only abnormally expressed in various tumor tissues but also involved in the pathogenesis of rheumatoid arthritis and knee osteoarthritis. 26-29 However, the interaction mechanism between LINC01534 and miR-140-5p in the development of OA is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A study examining the role of miR-144-3p in OA development in mice found that miR-144-3p was increased in the early stages of OA (Zhang et al, 2017). Our previous study also demonstrated that miR-144-3p is involved in the development of OA (Le et al, 2018). However, the role and function of the miRNA in OA pathogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 92%
“…Trong một nghiên cứu kiểm tra vai trò của miR-144-3p trong sự phát triển thoái hóa khớp ở chuột đã nhận thấy sự tăng biểu hiện của miR-144-3p ở giai đoạn đầu của thoái hóa khớp (Zhang, Lygrisse, & Wang, 2017). Tại Việt Nam, miR-144-3p được xác định có biểu hiện tăng trong thoái hoá khớp và đây là phân tử tiềm năng hỗ trợ trong chẩn đoán và điều trị nhiều bệnh ở người trong tương lai (Le, Ho, & Clark, 2018). Trước khi ứng dụng quy trình chẩn đoán và điều trị trong tương lai bằng cách sử dụng microRNA này, việc xác định chức năng của miR-144-3p là rất cần thiết.…”
Section: Giới Thiệuunclassified